SÍNTESE, CARACTERIZAÇÃO E ESTUDOS DE LIBERAÇÃO IN VITRO DE IBUPROFENATO INTERCALADO EM HIDRÓXIDOS DUPLOS LAMELARES DISPERSOS EM MEMBRANAS DE QUITOSANA/ALGINATO - Machado, Monielly Viomar (2019)
The layered double hydroxides (LDH) of Zn/Al in molar ratio 2:1 and 3:1 intercalated with the drug Ibuprofen (pharmacological grade reagent) were synthesized by the co-precipitation method at constant pH. These layered compounds were characterized by the XRD, FTIR and TGA/DSC instrumental techniques, which have shown the formation of the LDH containing the drug intercalated by the displacement to smaller angles in 2θ of the basal peak referring to the plane (003) and by the presence of the peaks referring to the (012) and (110), characteristic for layered compounds, observed by the XRD technique, characteristic stretching and bending deformations for the intercalated drug was observed by the FTIR technique, and it was possible to estimate the general formula for the LDH obtained through the results of TGA/DSC. After the LDH/IBU was characterized, the in vitro release of LDH in distilled water and phosphate buffer solution (PBS) were performed, where was observed the slower release of the drug into the medium. Thus, the synthesized LDH were added to the chitosan/alginate membranes, where the chitosan used was pharmacological grade, aiming at the use of low-cost reagents. In the in vitro release tests of the LDH contained in the membranes, it was possible to observe an increase in the insolubility of the drug that is intercalated in the interlayer space of these LDH, this increase in insolubility observed because the percentage of drug release was lower than the percentage of release of the drug in the free samples and visually by the translucency of the membranes. Thus, the following percentages of release 15,48% and 17,5% of the drug in water and 23,22% and 26,25% of the drug in PBS buffer respectively for the membranes samples containing the LDH Zn/Al-IBU 2:1 and Zn/Al-IBU 3:1. Thus, the synthesized hybrid membranes (chitosan/alginate - LDH-Ibuprofen) are very promising in the application as alloplastic bone graft with controlled release of drugs.